2015
DOI: 10.1177/0038038514557913
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and the Constitution of Friendship for Young Adults

Abstract: Friendship, sociologists suggest, is defined by institutionalized rules to a lesser degree than other important relationships. Hence it must be sustained through specific friendship-making practices. Social science literature tends to conceptualize friendship as enhancing the pleasures of alcohol use rather than as central to friendship production. This article examines alcohol as a technology in contemporary young adults' friendship-making. Interviews with 60 drinkers aged 18-24 years in Melbourne, Australia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 50 publications
(86 reference statements)
3
43
1
Order By: Relevance
“…This highlights the importance of health promotion activities that acknowledge the potential negative social consequences of reducing alcohol consumption. While not socialising in spaces where alcohol is normative might be more effective than attempting to continually resist normative pressures to drink for some people, for others, there is likely to be an enduring level of discontent associated with missed opportunities to socialise with old friends in familiar spaces . Therefore, there is a need for the development of health promotion activities that make not drinking in spaces such as licensed venues more acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the importance of health promotion activities that acknowledge the potential negative social consequences of reducing alcohol consumption. While not socialising in spaces where alcohol is normative might be more effective than attempting to continually resist normative pressures to drink for some people, for others, there is likely to be an enduring level of discontent associated with missed opportunities to socialise with old friends in familiar spaces . Therefore, there is a need for the development of health promotion activities that make not drinking in spaces such as licensed venues more acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…While not socialising in spaces where alcohol is normative might be more effective than attempting to continually resist normative pressures to drink for some people, 3 for others, there is likely to be an enduring level of discontent associated with missed opportunities to socialise with old friends in familiar spaces. 24 Therefore, there is a need for the development of health promotion activities that make not drinking in spaces such as licensed venues more acceptable. Shifting social and cultural norms in environments is a complex and slow process; 25 in the meantime providing strategies and techniques for how to present the decision to not drink in a culturally legitimate way may provide some benefit to non-drinkers, 4 along with strategies for disclosure of non-drinking in ways that minimises the "threat" of non-drinking to drinkers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, round buying allowed participants to care for one another on a night out by paying for a greater share of rounds for friends (MacLean, 2016). In this manner, friends who couldn't afford alcoholic drinks could still attend outings and drinking activities.…”
Section: Round Buying and Sociabilitymentioning
confidence: 99%
“…) and the research that has been done has focused on young people and/or binge drinking in public venues (Hughes et al . , Maclean ).…”
Section: Preventing the Misuse Of Alcoholmentioning
confidence: 99%
“…The scientific evidence here is as yet relatively sparse (though not we suspect the market research evidence!). A recent large scale scoping review found little evidence relating to the contexts of alcohol related behaviour (Hollands et al 2013) and the research that has been done has focused on young people and/or binge drinking in public venues (Hughes et al 2011, Maclean 2016.…”
Section: Preventing the Misuse Of Alcoholmentioning
confidence: 99%